The Analysis of Reading Comprehension Questions Found in the Text Book for Health Students in Poltekes Padang: Bloom Taxonomy - Rahmi Mardianti; Yetti Zainil (Universitas Negeri Padang, 2021)
Abstract The level of reading comprehension questions is very important for students especially English for Specific Purpose students. This research aims to find out the levels of reading comprehension questions and to investigate the English lecturers’ opinions related to the levels of reading comprehension questions based on Revised Taxonomy Bloom used in reading questions on English for Health course book. This study used a descriptive study that tries to portray the use of Taxonomy Blooms revise used in English course book for health students. This research used an English course book for health students entitled “English for Health” by Eka Susilowati and Agustin Widiani. The instruments of this research were observation checklist and interview guide. The observation checklist contained six components of the cognitive process of Revised Bloom’s Taxonomy. There were two findings of this research, they were: first, the levels of reading comprehension questions based on Revised Taxonomy Bloom used in reading questions on English for Health textbook was lower order thinking. Second, based on the English teachers’ opinion there were three adjustments that were made by the English teacher to the tasks in order to cater for higher order thinking process in the classroom. First, the teachers modify the questions based on the passage from other teaching material, the teachers make some questions which included higher level of thinking based on the passage that has been read before, the teachers give some projects to the students. Key words: Reading Comprehension Question, Bloom Taxonomy, English for Health Course Book